The impact of social media on the development of social anxiety: a systematic review - Xiaodan, Wang; Marof, Aini Azeqa; Abdullah, Haslinda; Tiantian, Ma (Human Resource Management Academic Research Society, 2023)
Social media addiction and information overload may have an influence on mental health. The purpose of this study is to synthesize the evidence from the last decade in order to improve our understanding of social media and social anxiety. A systematic assessment of the databases Web of Science, Scopus, and PubMed yielded 17 papers that addressed the study objectives set by the PRISMA declaration (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Four topics which were divided into 12 sub-themes emerged from the examination: social media users, social media types, social media use, and the relationship between social media and social anxiety. This study makes three significant contributions. First, an overview of social media and social anxiety research is offered. Second, a systematic review focuses on the role of social media on social anxiety. Finally, based on this systematic study, we did a variable analysis. The findings indicate that the mechanism of social media's influence on social anxiety requires additional investigation. To far, most research have focused on cross-sectional examinations, and additional experimental and longitudinal designs are needed to explain the situation in diverse groups and study potential links and potential mediators between social media and social anxiety